2020
DOI: 10.3390/ijerph17114089
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Green Brand Affect on Green Purchase Intentions: The Mediation Effects of Green Brand Associations and Green Brand Attitude

Abstract: This study investigates the impact of green brand affect on green purchase intentions and explores the mediation effects of green brand attitude and green brand associations by means of the structural equation model (SEM). There is no previous literature discussing the relationship between brand affect and purchase intentions from the perspective of green marketing. Therefore, this article establishes a green purchase intention framework to fill in the research gap. The research object of this study focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 68 publications
7
85
1
8
Order By: Relevance
“…A study in Egypt (Mostafa, 2007) concluded that consumer knowledge about environmental problems is an important factor that influences consumer attitudes to be more environmentally friendly. Previous research has found that attitudes play an important role in influencing consumer purchase intentions (Chen & Chang 2016). Furthermore, the gap found in the previous study regarding the influence of Environmental Knowledge on Green Purchase Intention encouraged the writer to include Attitude towards green product as a mediating variable, which then formulated the hypothesis as follows:…”
Section: H3: Environmental Knowledge Has a Positive Effect On Consumementioning
confidence: 99%
“…A study in Egypt (Mostafa, 2007) concluded that consumer knowledge about environmental problems is an important factor that influences consumer attitudes to be more environmentally friendly. Previous research has found that attitudes play an important role in influencing consumer purchase intentions (Chen & Chang 2016). Furthermore, the gap found in the previous study regarding the influence of Environmental Knowledge on Green Purchase Intention encouraged the writer to include Attitude towards green product as a mediating variable, which then formulated the hypothesis as follows:…”
Section: H3: Environmental Knowledge Has a Positive Effect On Consumementioning
confidence: 99%
“…as these keyword terms belong to the red-colored cluster. The recent literature also recognizes that academic research concerning green products is advancing considerably in the areas of greenwashing [ 70 , 71 ], environmental knowledge [ 72 ], green consumption [ 73 ], green purchase intention [ 74 , 75 ], green branding and loyalty [ 76 ], health consciousness [ 77 ], etc. in recent times.…”
Section: Bibliometric Analysis Of Literature: Resultsmentioning
confidence: 99%
“…19 The same study found that 66% of consumers say they are willing to pay more for sustainable brands. According to Chen et al (2020), green brands are those brands that consumers associate with environmental sustainability and particularly appeal to consumers who care about environmental protection. 20 Due to the increasing recognition and awareness of environmentalism in the market, the positioning of green branding strategies is to build up a unique sustainable image in the targeted customers, in order to meet their green claims.…”
Section: How Can Biobased Products Help Brand Image?mentioning
confidence: 99%
“… 20 Since more and more consumers are willing to give priority to greenness, by developing positive emotional responses as the basis for green brand influence, brand differentiation and generating green purchase intentions are crucial to green brand strategies. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%